Differential expression of HAVCR2 gene in pan-cancer: A potential biomarker for survival and immunotherapy - Li, Hetong; Yang, Dinglong; Hao, Min; Liu, Hongqi (Frontiers in Genetics, 2022)
T-cell immunoglobulin mucin 3 (TIM3) has emerged as promising immune checkpoint target in cancer; however, the hepatitis A virus cellular receptor 2 (HAVCR2) gene encoding TIM3 expression profile is still obscure, along with its value within cancer immunity and patient prognosis. The present study comprehensively analyzed HAVCR2 expression patterns in pan cancer try to verify the potential value for immunotherapy with checkpoint inhibitors. Our results displayed HAVCR2 differentially expressed and closely corresponded to survival status in pan cancer. More importantly, the HAVCR2 level was also significantly related to the degree of cancer immune infiltration, immune checkpoint genes, immune marker genes. Enrichment analyses implicated HAVCR2-associated terms in cancer, including immunity, metabolism, and inflammation. Our study demonstrated that HAVCR2 may participate in differing degrees of immune infiltration during cancer formation. The highlights of HAVCR2 pathway can contribute to further understanding the mechanism of it acting as both a biomarker and clinical target to improve therapeutic efficacy of immunotherapy.